2019
DOI: 10.5194/acp-19-10497-2019
|View full text |Cite
|
Sign up to set email alerts
|

Large contribution of meteorological factors to inter-decadal changes in regional aerosol optical depth

Abstract: Abstract. Aerosol optical depth (AOD) has become a crucial metric for assessing global climate change. Although global and regional AOD trends have been studied extensively, it remains unclear what factors are driving the inter-decadal variations in regional AOD and how to quantify the relative contribution of each dominant factor. This study used a long-term (1980–2016) aerosol dataset from the Modern-Era Retrospective Analysis for Research and Applications, version 2 (MERRA-2) reanalysis, along with two sate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(110 citation statements)
references
References 104 publications
10
99
1
Order By: Relevance
“…Figure 2 shows also that MODIS and MERRA-2 somewhat overestimate and underestimate AOD, respectively, with respect to AERONET AOD when the full period is taken into consideration. The underestimation in AOD by MEERA-2 is in line with previous studies that investigated AOD globally (Che et al [2]; Shi et al [47]; Buchard et al [48]). However, with a focus on storm episodes of mineral dust over four sunphotometer ground-based sites in Australia, Mukkavilli et al [49] found overestimation in MEERA-2 AOD.…”
Section: Time Series Of Modis Merra-2 and Aeronet Aosupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 2 shows also that MODIS and MERRA-2 somewhat overestimate and underestimate AOD, respectively, with respect to AERONET AOD when the full period is taken into consideration. The underestimation in AOD by MEERA-2 is in line with previous studies that investigated AOD globally (Che et al [2]; Shi et al [47]; Buchard et al [48]). However, with a focus on storm episodes of mineral dust over four sunphotometer ground-based sites in Australia, Mukkavilli et al [49] found overestimation in MEERA-2 AOD.…”
Section: Time Series Of Modis Merra-2 and Aeronet Aosupporting
confidence: 91%
“…Anthropogenic aerosols influence the Earth's radiation budget and climate directly by scattering solar light in the cloud-free atmosphere and indirectly by changing the cloud properties [1,2]. Anthropogenic aerosols on the whole cool the climate, while black carbon and mineral dust absorb solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the spatial patterns and seasonal variations of AOD trends in this study are consistent with previous studies of AOD evolution (e.g., Che et al, 2019) and suggest a relatively high degree of consistency in AOD trends between the three data sets. The results thus provide confidence in use of MERRA-2 to examine causes and consequences of these trends.…”
Section: 1029/2019jd031137supporting
confidence: 91%
“…The time series of Multi-angle Imaging SpectroRadiometer (MISR) images shows that the Gobi Desert accounts for >75% of the dust emission events in east Asia [13]. As a result of the long-distance transport of dust particles in the upper atmosphere, dust particles can change the atmospheric conditions at a regional or even global scale [14][15][16]. Dust aerosols from the Taklimakan and Gobi deserts can travel thousands of miles, affecting large areas of China [9,[17][18][19], Korea and Japan [20], and even the north Pacific and North America [21,22].…”
Section: Introductionmentioning
confidence: 99%